Implications of X‐ray beam profiles on qualitative and quantitative synchrotron micro‐focus X‐ray fluorescence microscopy. (28th September 2018) - Morrell, Alexander P.; Mosselmans, J. Frederick W.; Geraki, Kalotina; Ignatyev, Konstantin; Castillo-Michel, Hiram; Monksfield, Peter; Warfield, Adrian T.; Febbraio, Maria; Roberts, Helen M.; Addison, Owen; Martin, Richard A.
Abstract : The presence of image artefacts within synchrotron‐radiation X‐ray‐fluorescence microscopy is reported here. These artefacts can be attributed to the profile of the X‐ray beam; two correction methods have been developed to improve qualitative and quantitative synchrotron radiation X‐ray fluorescence mapping and are presented here. Abstract : Synchrotron radiation X‐ray fluorescence microscopy is frequently used to investigate the spatial distribution of elements within a wide range of samples. Interrogation of heterogeneous samples that contain large concentration ranges has the potential to produce image artefacts due to the profile of the X‐ray beam. The presence of these artefacts and the distribution of flux within the beam profile can significantly affect qualitative and quantitative analyses. Two distinct correction methods have been generated by referencing the beam profile itself or by employing an adaptive‐thresholding procedure. Both methods significantly improve qualitative imaging by removing the artefacts without compromising the low‐intensity features. The beam‐profile correction method improves quantitative results but requires accurate two‐dimensional characterization of the X‐ray beam profile.